2013
DOI: 10.1139/cjpp-2012-0261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise on monocrotaline-induced changes in right heart function and pulmonary artery remodeling in rats

Abstract: Pulmonary arterial hypertension (PAH) induced by monocrotaline (MCT) is an experimental protocol of right heart failure. We analyzed the role of exercise training on the right ventricle structure and function, pulmonary artery remodeling, and GSK-3β expression. Rats were divided among the following groups: sedentary control (SC), sedentary monocrotaline (SM), trained control (TC), and trained monocrotaline (TM). Rats underwent exercise training for a period of 5 weeks, with 3 weeks post-MCT injection. Rats in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 35 publications
4
60
3
3
Order By: Relevance
“…This increase in pulmonary pressure seems to be insufficient to induce RV hypertrophy, as was demonstrated in this study, which corroborates previous data from our laboratory (Siqueira et al 2011). This outcome differed from that observed in male rats, where an evident RV hypertrophy was documented (Colombo et al 2013). These findings agree with reports showing that female rats develop less PAH in response to MCT than males (Bal et al 2013).…”
Section: Discussionsupporting
confidence: 77%
“…This increase in pulmonary pressure seems to be insufficient to induce RV hypertrophy, as was demonstrated in this study, which corroborates previous data from our laboratory (Siqueira et al 2011). This outcome differed from that observed in male rats, where an evident RV hypertrophy was documented (Colombo et al 2013). These findings agree with reports showing that female rats develop less PAH in response to MCT than males (Bal et al 2013).…”
Section: Discussionsupporting
confidence: 77%
“…Studies in animal models of pulmonary hypertension have shown that exercise training is associated with improvement in endothelium-dependent relaxation in the pulmonary circulation, favorable remodeling of pulmonary vasculature, and reduced right ventricle enddiastolic pressure. 45,46 Furthermore, recent human studies have shown that exercise training is associated with significant improvements in central pulmonary perfusion and peripheral skeletal muscle function, which could also contribute to the training-related improvement in exercise capacity. 16,23 In this study, we observed a significant improvement in the pulmonary arterial systolic pressure with training, which could lead to significant reductions in pulmonary vascular resistance and a concomitant improvement in blood flow through the pulmonary vascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the same study, exercise training was associated with reductions in pulmonary artery diameters (-46%, p < 0.05), interstitial volume (-60%, p < 0.05) and right ventricular end-diastolic pressure (-45%, p < 0.05) [16]. The authors found a 37% reduction (p < 0.05) in the ratio between the phosphorylated (inactive/prohypertrophic) and the dephosphorylated (active/antihypertrophic) form of glycogen synthase kinase [16]. These results led the authors to speculate that glycogen synthase kinase signaling is probably involved in the positive effects of exercise training in PH.…”
Section: Possible Molecular Effects Of Exercise Training On Phmentioning
confidence: 99%
“…Another animal model with Wistar rats using the same exercise protocol revealed significant improvement in capillary density (+86%, p < 0.05), up to near-normal values [16]. Furthermore, in the same study, exercise training was associated with reductions in pulmonary artery diameters (-46%, p < 0.05), interstitial volume (-60%, p < 0.05) and right ventricular end-diastolic pressure (-45%, p < 0.05) [16].…”
Section: Possible Molecular Effects Of Exercise Training On Phmentioning
confidence: 99%